Perkembangan Moral Siswa SMP Tentang Permasalahan Pertanian Pasang Surut di Kabupaten Banjar Melalui Penyelesaian Masalah - Ruhena Ruhena; Yudi Firmanul Arifin; Aminuddin Prahatama Putra (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2021)
Moral is the ability to understand the values in society about the views of good-bad, right-wrong, what individuals should and should not do in community groups. The moral development of adolescents is more mature and more familiar with moral values or the concept of morality compared to the age of children. The problem of tidal agriculture was raised as a moral dilemma case, so that the stages and characteristics of students' moral development in solving problems were obtained. The purpose of this study was to describe the stages of moral development of the students of SMP Negeri 1 Gambut on the problems of tidal agriculture in Banjar Regency. The research method used is a qualitative approach and the type of descriptive research. The research aid instrument was in the form of an early test of moral development using the Defining Issue Test (DIT), written assignments, and interviews. The results showed that the stages of moral development of junior high school students regarding tidal agricultural problems in Banjar Regency through problem solving were in stages 2, 3, and 4.